Cerebral Volumetric Changes Induced by Prolonged Hypoxic Exposure and Whole-Body Exercise. Issue 11 (November 2014) - Rupp, Thomas; Jubeau, Marc; Lamalle, Laurent; Warnking, Jan M; Millet, Guillaume Y; Wuyam, Bernard; Esteve, François; Levy, Patrick; Krainik, Alexandre; Verges, Samuel
The present study assessed the isolated and synergetic effects of hypoxic exposure and prolonged exercise on cerebral volume and subedema and symptoms of acute mountain sickness (AMS). Twelve healthy males performed three semirandomized blinded 11- hour sessions with (1) an inspiratory oxygen fraction (FiO2 ) of 12% and 4-hour cycling, (2) FiO2 = 21% and 4-hour cycling, and (3) FiO2 = 8.5% to 12% at rest (matching arterial oxygen saturation measured during the first hypoxic session). Volumetric, apparent diffusion coefficient (ADC), and arterial spin labelling 3T magnetic resonance imaging sequences were performed after 30 minutes and 10 hours in each session. Thirty minutes of hypoxia at rest induced a significant increase in white-matter volume (+0.8 ± 1.0% compared with normoxia) that was exacerbated after 10 hours of hypoxia at rest (+1.5 ± 1.1%) or with cycling (+1.6 ± 1.1%). Total brain parenchyma volume increased significantly after 10 hours of hypoxia with cycling only (+1.3 ± 1.1%). Apparent diffusion coefficient was significantly reduced after 10 hours of hypoxia at rest or with cycling. No significant change in cerebral blood flow was observed. These results demonstrate changes in white-matter volume as early as after 30 minutes of hypoxia that worsen after 10 hours, probably due to cytotoxic edema. Exercise accentuates the effect of hypoxia by increasing total brain volume. These changes do not however correlate with AMS symptoms.